Asymptotics for Nonlinear Evolution Equation with Module-Fractional Derivative on a Half-Line. (29th June 2010) - Árciga A, Martín P.
Abstract : We consider the initial-boundary value problem for a nonlinear partial differential equation with module-fractional derivative on a half-line. We study the local and global in time existence of solutions to the initial-boundary value problem and the asymptotic behavior of solutions for large time.